Respuestas
Respuesta dada por:
2
a)17y-y+9=32-19y+82
16y+19y=114-9
35y=105
y=105/35
y=3
b) 2[3x+1-2(x+4)]-(3x+5)=0
2[3x+1-2x-8]-3x-5=0
6x+2-4x-16-3x-5=0
-x-19=0
x=-19
c) -3+x-5[2x+4-(x+2)]=x+2
-3+x-5[2x+4-x-2)]=x+2
-3+x-10x-20+5x+10=x+2
5x=-15
x=-3
d) (x-2)²-(3-x)²=1
x²-4x+4-(9-6x+x²)=1
x²-4x+4-9+6x-x²=1
2x=1+5
x=6/2
x=3
e) (x-2)²+x(x-3)=3(x+4)(x-3)
x²-4x+4+x²-3x=3(x²-3x+4x-12)
2x²-7x+4=3x²-9x+12x-36
4=x²+10x-36
x²+10x-40=0
Aplicando formula general:
![x=-b+- \sqrt{b^2-4ac} /2a x=-b+- \sqrt{b^2-4ac} /2a](https://tex.z-dn.net/?f=x%3D-b%2B-+%5Csqrt%7Bb%5E2-4ac%7D+%2F2a)
![x1=-10+ \sqrt{10^2(1)(-40)}/2(1)= \sqrt{65}-5 x1=-10+ \sqrt{10^2(1)(-40)}/2(1)= \sqrt{65}-5](https://tex.z-dn.net/?f=x1%3D-10%2B+%5Csqrt%7B10%5E2%281%29%28-40%29%7D%2F2%281%29%3D+%5Csqrt%7B65%7D-5++)
![x2=-10- \sqrt{10^2(1)(-40)}/2(1)=- \sqrt{65}-5 x2=-10- \sqrt{10^2(1)(-40)}/2(1)=- \sqrt{65}-5](https://tex.z-dn.net/?f=x2%3D-10-+%5Csqrt%7B10%5E2%281%29%28-40%29%7D%2F2%281%29%3D-+%5Csqrt%7B65%7D-5)
16y+19y=114-9
35y=105
y=105/35
y=3
b) 2[3x+1-2(x+4)]-(3x+5)=0
2[3x+1-2x-8]-3x-5=0
6x+2-4x-16-3x-5=0
-x-19=0
x=-19
c) -3+x-5[2x+4-(x+2)]=x+2
-3+x-5[2x+4-x-2)]=x+2
-3+x-10x-20+5x+10=x+2
5x=-15
x=-3
d) (x-2)²-(3-x)²=1
x²-4x+4-(9-6x+x²)=1
x²-4x+4-9+6x-x²=1
2x=1+5
x=6/2
x=3
e) (x-2)²+x(x-3)=3(x+4)(x-3)
x²-4x+4+x²-3x=3(x²-3x+4x-12)
2x²-7x+4=3x²-9x+12x-36
4=x²+10x-36
x²+10x-40=0
Aplicando formula general:
Preguntas similares
hace 7 años
hace 7 años
hace 9 años